Doğum öncesi ve 0-2 yaş gelişimi (Kur’an-ı Kerim ayetleri ışığında) - Çamdibi, Ayşe Ümran (My University, 1999)
In view of the fact the early years of human developmental and educational process are of great significance, the present study makes an attempt to find out the importance of pre-natal and the first two years of post-natal development. It is beyond doubt that educating children is a difficult task. It is, therefore, a must for the parents to discover their children's physical and spiritual characteristics. This thesis attempts to help parents understand that physical and spiritual characteristics of children develop as a whole. It is of great mistake to concentrate on only physical development. Every child has his own kind of psychical development and this begins to grow at birth. It is argued in this thesis that environmental factors are decisive to shape his/ her character in a particular way towards becoming an adult. Bearing in mind the nature of education Chapter One deals with couples' responsibility towards forming a union in the family in view of related Qur'anic verses and scientific findings. Findings of this thesis confirm the view that Qur'anic verses and scientific findings support one another. The chapter also presents foetus' development from six week onwards. Chapter Two and Three examine developmental stages of the early years of childhood up to age two, especially in infancy in the light of scientific research and the Prophetic Tradition (Sunnah). They conclude that the years from birth to age two are very significant in terms of children's physical, moral and personal development. In short, the present study makes an attempt to get couples know these facts before they establish a family. It also tries to make parents efficient in bringing up their children as well as being aware of the features of different developmental stages.
Keywords: DOĞUM-SOSYAL YÖNLERİ,ÇOCUK YETİŞTİRME,İSLAMDA